国际图画书大奖作品在中国的引介 ——以凯迪克奖和凯特·格林纳威奖为例: Introduction of International Picture BookAward Winning Works in China – A Case Study of the Caldecott Medal and the Kate Greenaway Medal - Bian Liping (ERUDITE: Journal of Chinese Studies and Education, 2024)
儿童图画书在欧美国家已发展了百余年，但真正在中国流行不过二十多年的时间，而且是随着外国图画书在中国的引进，才流传开来。荣获国际图画书大奖的图书，因其可靠的品质一直是中国出版商首选的引入对象。本文以美国凯迪克奖和英国凯特·格林纳威奖获奖作品为例，通过对其引进情况进行分析和对代表作品的文本分析，探讨国际图画书奖获奖作品对中国图画书创作的启发作用。研究表明，获奖图画书的引进对于中国原创图画书的质量提升、推动中国图画书市场国际化与文化交流、促进中国本土图画书奖项的成立方面都有促进作用。 Children’s picture books have been developed in Europe and American countries for over a century, but they have only gained popularity in China for a little more than two decades. This popularity has been largely driven by the introduction of foreign picture books to China. Books that have won international picture book awards have consistently been the preferred choice for Chinese publishers due to their reliable quality. This paper takes award-winning works from the American Caldecott Medal and the British Kate Greenaway Medal as examples to explore the inspirational role of the award-winning works of the International Picture Book Awards for the creation of Chinese picture books through the analysis of their introduction and the textual analysis of the representative works. The study shows that the introduction of award-winning picture books has contributed to the quality improvement of Chinese original picture books, the promotion of the internationalization of Chinese picture book market and cultural exchanges, as well as the promotion of the establishment of Chinese local picture book awards. Keywords: Picture book; Picture book Award; Introduction of picture books; Children’s reading